2019
DOI: 10.20964/2019.04.48
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pulsed Current Parameters on Porosity of Copper Prepared by Jet Electrodeposition

Abstract: Surface texturing has become an increasingly prevalent approach to improve the tribological properties of materials. The present work aims to study a novel texturing technology. A copper coating with a porous surface structure was directly prepared on stainless steel using a copper sulfate solution bath via high-speed jet electrodeposition. A fine, uniform honeycomb structure with micron sized pores can be achieved using a pulsed current. The duty cycle, current density and current frequency of the pulsed curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It is observed that the value of the current increases with an increase in voltage. The increased applied voltage also leads to an increase in the size of the nodules (Fan et al , 2019b; Tian et al , 2010), as observed in the FESEM morphology images of the deposited bead surfaces [Figures 7(c), 8(c) and 9(c)]. In addition, a rise in voltage causes the entire deposited layer to grow in a cellular manner, which is followed by larger grain size, increased surface roughness, decreased density and worsened surface flatness, as observed in the surface morphology analysis by 3D profilometer [Figures 7(b), 8(b) and 9(b)].…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the value of the current increases with an increase in voltage. The increased applied voltage also leads to an increase in the size of the nodules (Fan et al , 2019b; Tian et al , 2010), as observed in the FESEM morphology images of the deposited bead surfaces [Figures 7(c), 8(c) and 9(c)]. In addition, a rise in voltage causes the entire deposited layer to grow in a cellular manner, which is followed by larger grain size, increased surface roughness, decreased density and worsened surface flatness, as observed in the surface morphology analysis by 3D profilometer [Figures 7(b), 8(b) and 9(b)].…”
Section: Resultsmentioning
confidence: 99%